The impacts of climate change on Greek airports - Gratton, Guy; Padhra, Anil; Rapsomanikis, Spyridon; Williams, Paul D. (Springer, 2020)
Time series of meteorological parameters at ten Greek airports since 1955 indicated the level of climate change in the Eastern Mediterranean area. Using this data, take-off performance was analysed for the DHC-8-400—a typical short range turboprop airliner, and the A320, a typical medium scale turbofan airliner. For airports with longer runways, a steady but unimportant increase in take-off distances was found. For airports with shorter runways, the results indicate a steady reduction in available payload. At the most extreme case, results show that for an Airbus A320, operating from the, relatively short, 1511m runway at Chios Airport, the required reduction in payload would be equivalent to 38 passengers with their luggage, or fuel for 700 nautical miles (1300 km) per flight, for the period between the A320’s entry to service in 1988 and 2017. These results indicate that for airports where aeroplane maximum take-off mass is a performance limited function of runway length, and where minimum temperatures have increased and/or mean headwind components decreased, climate change has already had a marked impact on the economic activity in the airline industry. Similar analyses could be usefully carried out for other runway-length–limited airports, which may often include island airports. It is also noted that previous research has only considered temperature effects, and not wind effects. Wind effects in this study are less significant than temperature, but nonetheless have an effect on both field performance noise and pollution nuisance around airports.
Keywords: Airport; Runway; Take-Off Performance; Aeroplane; A320; DHC-8-400; Greece; Mediterranean